2012
DOI: 10.12659/msm.883487
|View full text |Cite
|
Sign up to set email alerts
|

Importance of anemia in the chronic Cardiorenal syndrome: Effects on renal function after heart transplantation

Abstract: SummaryBackgroundCardiorenal syndrome has been recently divided into 5 categories, according to acute or chronic evolution and primary organ dysfunction. Anemia can also accompany this disorder, leading to a more complex situation. This study aims to analyze the renal outcomes of patients, specifically patients with chronic Cardiorenal syndrome, with or without anemia, long-term after heart transplantation.Material/MethodsThis was a retrospective cohort study on chronic Cardiorenal syndrome patients submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…In addition, paired sample analyses combining the development of renal function following consecutive LVAD and HTx in the same patients are scant. Some research suggests that HTx following LVAD leaves the downward trend unaltered [ 71 ] although others report that HTx may temporarily increase GFR in patients with prior compromised renal function [ 72 ]. Singh et al [ 56 ] retrospectively analyzed the evolution of renal function of 116 patients consecutively undergoing MCS and HTx.…”
Section: Renal Function In the Long Runmentioning
confidence: 99%
“…In addition, paired sample analyses combining the development of renal function following consecutive LVAD and HTx in the same patients are scant. Some research suggests that HTx following LVAD leaves the downward trend unaltered [ 71 ] although others report that HTx may temporarily increase GFR in patients with prior compromised renal function [ 72 ]. Singh et al [ 56 ] retrospectively analyzed the evolution of renal function of 116 patients consecutively undergoing MCS and HTx.…”
Section: Renal Function In the Long Runmentioning
confidence: 99%
“…Los pacientes con hemoglobina < 10 mg/dL fueron excluidos de este estudio para evitar que pacientes con ERC no diagnosticada (que usualmente tienen hemoglobinas bajas) fueran incluidos en el mismo y también para evitar que la presencia de una baja hemoglobina sea otro factor confusor ya que al haber menos hemoglobina hay menor transporte de oxígeno y por lo tanto todos los tejidos incluidos el riñón sufren de una menor oxigenación. Sin embargo, este estudio mostró una asociación entre una mayor hemoglobina y la presencia de SCR1, que si bien no concuerda con la fisiopatología propuesta para el desarrollo de síndrome cardiorrenal en general, nos indica que en la fisiopatología del SCR1 la anemia no es una variable asociada de forma inversa (a menor hemoglobina, mayor frecuencia de síndrome cardiorrenal) como sí lo es en el síndrome cardiorrenal crónico o tipo 2 35 . Esta asociación inversa ha sido ya observada en un estudio donde se demostró que la hemoconcentración durante la primera semana de los pacientes que ingresan con falla cardíaca agudamente descompensada se asoció a una peor función renal 36 .…”
Section: Discussionunclassified
“…The risk of the CIN increased in the presence of chronic renal failure, diabetes mellitus (DM), congestive heart failure (CHF), advanced age, anemia, female gender, dehydration and excess usage of contrast agent [ 4 , 15 ]. It is found that presence of anemia is a marker for renal function non-recovery in a group of heart transplanted patients with cardiorenal syndrome [ 16 ].…”
Section: Introductionmentioning
confidence: 99%